2020
DOI: 10.1097/pcc.0000000000002131
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Closure for the Treatment of Deep Sternal Wound Infection After Pediatric Cardiac Surgery

Abstract: Objectives: Vacuum-assisted closure is being increasingly used to treat deep sternal wound infection following cardiac surgery, but most of the data refer to adults. This study investigated the safety and efficacy of vacuum-assisted closure in pediatric patients. Design: Retrospective file review. Setting: Tertiary pediatric medical center. Patients: All children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 25 publications
0
24
0
4
Order By: Relevance
“…Sternal wounds of all but seven patients were healed after VAC therapy without further operations. Additional closure using muscle flap or skin graft was necessary in seven patients (7/201, 3.5%) to approximate the sternal wounds 15,16,18,20,22 . Follow‐up data were only provided in three studies 14,18,19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sternal wounds of all but seven patients were healed after VAC therapy without further operations. Additional closure using muscle flap or skin graft was necessary in seven patients (7/201, 3.5%) to approximate the sternal wounds 15,16,18,20,22 . Follow‐up data were only provided in three studies 14,18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Five case series studies 14,17,18,20,22 reported overall mortality, and the pooled estimate of overall mortality was 5.8% (95% CI, 2.5%-9.1%, I 2 = 0%, Figure 3B). However, only two deaths resulted from severely infectious complications, one from sepsis and the other from infectious endocarditis.…”
Section: Mortalitymentioning
confidence: 99%
“…Although it usually leads an uneventful course, application of NPWT in pediatric patients necessitates special considerations. 12 The first concern is that the threshold value for causing circulatory instability may be exceptionally lower in small patients, so that NPWT might cause exsanguination and rupture of fragile vital organs. Therefore, a lower negative pressure (À25 to À75 mm Hg) is usually recommended in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a lower negative pressure (À25 to À75 mm Hg) is usually recommended in these patients. 12,13 The other issue is the small dimension of the wound in infants. To overcome, Padalino et al 8 suggested a modification called "two-layer technique" and prevented the damage of surrounding tissues by correct positioning of the connecting tube.…”
Section: Discussionmentioning
confidence: 99%
“…8 Negative pressure wound treatment is also increasingly implemented to manage various difficult-to-treat wounds in children. [9][10][11] A tight and adhesive film dressing on the skin surrounding the wound is typically used and vital to prevent leakage and enable the build-up of negative pressure.…”
Section: Introductionmentioning
confidence: 99%